Application of hypoxicators in the rowers' training - S. Neykov; V. Bachev; L. Petrov; A. Alexandrova; S. Andonov; S. Kolimechkov (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Intermittent altitude exposure leads to improvements in aerobic performance and blood parameters of athletes. The variety of hypoxic devices and simulated altitude training models requires a detailed study of their effects to achieve the best results. The aim of this study was to investigate the effect of a four-week training camp at sea level conditions, combined with normobaric hypoxia, provided by hypoxicators during the night's sleep of the athletes. Sixteen rowers of the Bulgarian national team (17.13±0.83 years old) were divided into a control group (n=8) and an experimental group (n=8) subjected to hypoxia for a period of four weeks. At the beginning and end of the training camp, anthropometric and hematological data were measured. A submaximal test on the Concept II rowing ergometer was performed, and the physical work capacity and anaerobic threshold were determined. The results showed: 1) a lack of significant changes in the aerobic performance after training camp, both within and between groups; 2) at the end of the training camp in the experimental group a statistically significant increase in hemoglobin concentration (156.25±4.11 vs 162.75±4.11 g/L, p<0.01) and erythrocyte count (5.26±0.13 vs 5.49±0.10 g/L, p<0.01) was observed. The encouraging results regarding the higher increase in blood oxygen-carrying capacity in the experimental group did not lead to an increased working capacity. Further research should be provided in the search for optimal hypoxic training parameters, allowing not only a rise in hemoglobin concentration, but also the preservation of blood rheological properties.